Teacher experiences of delivering an obesity prevention programme (The WAVES study intervention) in a primary school setting. (November 2015) - Griffin, Tania L; Clarke, Joanne L; Lancashire, Emma R; Pallan, Miranda J; Passmore, Sandra; Adab, Peymane
Objective: There has been a wealth of childhood obesity prevention studies in school-based settings. However, few have investigated the experiences of school staff charged with delivery of such programmes. This study aimed to elicit teachers' experiences of delivering a childhood obesity prevention programme for children aged 6–7 years. Design: Descriptive-interpretive qualitative study. Setting: Primary schools participating in the UK West Midlands ActiVe lifestyle and healthy Eating in School children (WAVES) study. Method: In all, 14 teachers were recruited from 12 primary schools. Semi-structured interviews were conducted and data analysis was guided by the Framework Approach. Results: Teachers recognised the importance of obesity prevention in primary schools. They reported positively on aspects of the intervention, in particular its flexibility and the ready-prepared materials. Time constraints and gaining support of parents were seen as key challenges to intervention delivery. Conclusions: Delivering an obesity prevention programme in school is feasible but challenging for teachers. Our findings suggest that to maximise the likelihood of delivery, interventions should be hands-on, easy to manage and flexible to the needs of individual schools. The perceived importance of the promotion of healthy lifestyle behaviours by schools was evident, but teachers felt restricted in the resources that could be devoted to achieve and encourage this. National combined with local level direction and support for healthy lifestyles in children would help schools to give this the priority it requires.